Cómo formular una propuesta para la elaboración de un Proyecto Ambiental Escolar (PRAE) a través del estudio de las situaciones ambientales del Instituto Comercial Loreto ubicado en la localidad octava de Bogotá (Kennedy) (Papeles, 2009)
The school environmental projects (Proyectos Ambientales Escolares —PRAE—) are environmental education strategies which, from the classroom and the institution, are linked to the integral solution for the particular environmental problematic of a zone or a region. In this article, it is exposed a researching experience that socializes the formulation, construction and collective development of the PRAE with the community involved in the education of the Instituto Comercial Loreto located in the eighth zone of Kennedy. This presentation starts with the data collection and the description of the environmental situations found; then, it follows with a metholodology to identify the most critical situations that must be tackled, and finally, some alternatives for the solution to the environmental problematic are rised. The goal in this text aims at promoting and consolidating the true sense the PRAE was created and proposed in the Environmental National Education Policies as fundamental tools for changing and improving the quality of life for the people involved in these projects.
Keywords: Environmental education, School Environmental Project (PRAE), socio-cultural context, pedagogy, Environmental National Education Policies.